The Mongolian People's Republic : Toward a Market Economy - Sukachevin, Padej; Leimone, John.; Milne, Elizabeth; Rozwadowski, F. (Washington, D.C. : International Monetary Fund, 1991)
This paper is based on an IMF staff report prepared in connection with the application of the Mongolian People's Republic (Mongolia) for membership in the International Monetary Fund. It reviews Mongolia's political and economic history, highlighting its changing economic structure following World War II and its recent efforts to introduce market mechanisms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet